2016
DOI: 10.1038/srep27477
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interhemispheric synchrony in Parkinson’s disease with depression

Abstract: The alterations of interhemispheric resting-state functional connectivity (FC) in Parkinson’s disease (PD) with depression remain unclear, so we aimed to explore the differences of interhemispheric FC between PD with and without depression. Twenty-one depressed PD (DPD) patients, 49 non-depressed PD (NDPD) patients and 50 matched healthy controls (HC) participated in this study. Resting-state functional magnetic resonance imaging (fMRI) data were analyzed with the voxel-mirrored homotopic connectivity (VMHC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
2
15
1
Order By: Relevance
“…A PET study suggested that MSA patients with memory and frontal executive dysfunction tended to show hypometabolism in the anterior cerebellum and frontal cortex in the early stage of the disease ( Lyoo et al, 2008 ). In addition, the hypoactivity of the DLPFC in PD patients with depression has also been identified in previous studies ( Zhu et al, 2016 ). The impaired striatal cells in parkinsonism could lead to secondary frontal lobe dysfunction, including disruption of the cognitive loop linking the striatum with the DLPFC ( Jokinen et al, 2013 ).…”
Section: Discussionsupporting
confidence: 70%
“…A PET study suggested that MSA patients with memory and frontal executive dysfunction tended to show hypometabolism in the anterior cerebellum and frontal cortex in the early stage of the disease ( Lyoo et al, 2008 ). In addition, the hypoactivity of the DLPFC in PD patients with depression has also been identified in previous studies ( Zhu et al, 2016 ). The impaired striatal cells in parkinsonism could lead to secondary frontal lobe dysfunction, including disruption of the cognitive loop linking the striatum with the DLPFC ( Jokinen et al, 2013 ).…”
Section: Discussionsupporting
confidence: 70%
“…One study showed that depression was correlated with impaired color vision in PD patients through clinical observation and inferred that the visual system is crucial in the depressive pathology in PD patients ( 26 ). Some fMRI studies have shown that the value of regional homogeneity in the occipital lobe was decreased ( 27 ) and the synchrony of interhemispheric resting-state functional connectivity was impaired in the occipital lobe in d-PD patients ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our findings in depressed PD patients, white matter damage is more extensive in patients with primary depression, but all these impaired WM regions or fibers mainly located in the prefrontal cortex, limbic system, and the contact fibers between them. Studies using RS‐fMRI have also shown decreased functional connectivity between the prefrontal‐limbic networks and impaired interhemispheric synchrony in PD with depression patients. Therefore, the abnormal sensory integration and evaluation caused by white matter deficits which we found might be an important reason for depression in PD.…”
Section: Discussionmentioning
confidence: 99%